Breaking the book : print humanities in the digital age - Mandell, Laura (Chichester, West Sussex, UK : Wiley Blackwell, 2015)
"Breaking the Book compares and contrasts the print with the digital revolution, emphasizing that those with one foot in manuscript and coterie print cultures have much to reveal to those of us who straddle mass print and new media. Along with altering our notions of what constitutes a "book," the transformation of the printed page to digital text has forced us to question long-held methodologies in literary criticism. In this new manifesto, noted media and digital humanities scholar Laura Mandell explores the cognitive consequences and emotional effects of human interactions with physical books, revealing why the traditional humanities disciplines are resistant to "digital" humanities." -- Book jacket.
Pre-Bound -- Language by the Book -- Bound -- Print Subjectivity, or the Case History -- Distributed Reading, or the Critic Filter -- Unbound
Includes bibliographical references and index.
Print version record.
Keywords: Books -- Psychological aspects; Books and reading -- Technological innovations; Books -- Digitization -- Social aspects; LANGUAGE ARTS & DISCIPLINES / Publishing; LITERARY CRITICISM / Books & Reading; Electronic books; Electronic books